2022
DOI: 10.3390/molecules27051574
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbohydrate, High-Protein, and Gluten-Free Bread Supplemented with Poppy Seed Flour: Physicochemical, Sensory, and Spectroscopic Properties

Abstract: Background: This study aimed to determine the effect of poppy seed flour (PF) on the physicochemical and spectroscopic properties of low-carbohydrate, high-protein, and gluten-free bread. Methods: The changes at the molecular level were assessed in bread using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). Bread prepared with buckwheat, flaxseed, and pea protein was enriched with PF at a concentration of 5–15%. Results: The results showed that the pasting parameters of dough s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Samples with a higher share of WSF were characterized by a lower volume at the level of 1.46 g•cm −3 but comparable to the control bread (1.45 g•cm −3 ). According to our previous research, the addition of poppy or walnut flour to low-carbohydrate, gluten-free bread resulted in an increase in volume [31,32]. In the present studies, no decrease in this parameter was observed compared to the volume of control bread.…”
Section: Basic Properties Of Low-carbohydrate Bread With Different Am...supporting
confidence: 58%
“…Samples with a higher share of WSF were characterized by a lower volume at the level of 1.46 g•cm −3 but comparable to the control bread (1.45 g•cm −3 ). According to our previous research, the addition of poppy or walnut flour to low-carbohydrate, gluten-free bread resulted in an increase in volume [31,32]. In the present studies, no decrease in this parameter was observed compared to the volume of control bread.…”
Section: Basic Properties Of Low-carbohydrate Bread With Different Am...supporting
confidence: 58%
“…Based on our previous studies [ 41 , 42 , 43 , 44 , 45 ], the leftmost characteristic area of each spectrum ( Figure 6 ) shows the maximum at ~3290 cm −1 , assigned to the stretching vibrations of -OH (ν(-OH)) groups (both free and the hydrogen bound -OH groups cause bands in this region). Since the starch remains the main component of the biopolymers tested, this band most likely originates from -OH groups of amylose or amylopectin.…”
Section: Resultsmentioning
confidence: 94%
“…The next important area contains a signal with the maximum at ~1150 cm −1 , which originates mainly from the ring stretching vibrations in the main component of the samples. This was enhanced by the stretching vibrations of C-O bonds, as well as by the C-O-C (ν(C-O-C)) moieties of amylose and amylopectin molecules [ 45 , 49 ]. Another set of vibrations is represented by the bands with the maxima at ~1015 and 995 cm −1 , which correspond primarily to the C-O stretches that also are very characteristic for these types of biopolymer structure [ 41 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the values of bread crumb hardness were significantly lower and did not exceed 13 N. This is mainly due to the fact that wheat bread, compared to gluten bread, has a much larger volume and lower crumb density, which directly translates into lower hardness. Other authors [46] analyzed the texture of gluten-free bread with reduced carbohydrate content, enriched with poppy seed flour, and found significantly higher crumb hardness, which did not exceed 25 N, after both 24 and 48 h of storage. Similar values for gluten-free bread were observed by Wójcik et al [5], when enriching it with pea protein.…”
Section: Texture Parameter Resultsmentioning
confidence: 96%